PERAN PEMUDA DALAM PELESTARIAN SENI TRADISIONAL BENJANG GUNA MENINGKATKAN KETAHANAN BUDAYA DAERAH (Studi Di Kecamatan Ujungberung Kota Bandung Provinsi Jawa Barat) - Yaya Mulya Mantri (Jurnal Ketahanan Nasional, 2014)
ABSTRACTThe role of young man in preservation Benjang’s folk art was assessed as fair which included five roles which were: the role of endowment, the role of owner, the role of doer, the role of innovative, and role of educative. Young man faced fi ve constraints in Benjang’s folk art preservation, that was first of lack of fund in developing Benjang’s folk art, second lack of government involvement in Benjang’s folk art development, third there was no involvement of academician side in Benjang’s management management and folk art show packaging, fourth lack of understanding of artistic aesthetics the Benjang’s actors, and fifth the entry of foreign culture in massif. Implication to cultural resilience of area: increasing cultural awareness and identity of area, change without trespassing cultural originality of area, and penetrating cultural warded of strangers foreigners which unmatched to area culture.ABSTRAKPeran pemuda dalam pelestrian seni tradisional Benjang dinilai cukup baik yang mencakup lima peran yaitu: peran pewarisan, peran pemilik, peran pelaku, peran inovatif, dan peran edukatif. Pemuda menghadapi lima kendala dalam pelestarian seni tradisional Benjang, yaitu pertama kekurangan dana dalam mengembangkan seni tradisional Benjang, kedua kurangnya keterlibatan pemerintah dalam pengembangan seni tradisional Benjang, ketiga tidak ada keterlibatan dari pihak akademisi dalam pengelolaan manajemen dan pengemasan pertunjukan seni tradisional Benjang, keempat kurangnya pemahaman estetika seni para seniman Benjang, dan kelima masuknya budaya asing secara masif. Implikasi terhadap ketahanan budaya daerah: meningkat kesadaran dan identitas budaya daerah, perubahan tanpa menyalahi orisinalitas budaya daerah, dan menangkal penetrasi budaya asing yang tidak sesuai dengan budaya daerah.